DARK TIMES IN EKA KURNIAWAN’S NOVEL BEAUTY IS A WOUND - Nur Salaila; Asnani Asnani (JOURNAL OF LANGUAGE, 2022)
The purpose of this research is to find out the dark times experiences that the protagonist undergoes in the novel Beauty is A Wound written by Eka Kurniawan in i 2002. This novel tells the story of Dewi Ayu who is willing to be trampled by the power of the Japanese army, because Dewi Ayu wants to save her best friend’s mother. Dark times is a natural feeling which, if unfelt, will stay in one’s array of unresolved trauma knots. This research uses qualitative method in which the data are taken by quoting the relevant proofs from the novel then analyzing them and making the conclusion in the description forms. The findings show that the dark times undergone by the protagonist’s gives negative impact to her life. The dark times period experienced by the protagonist covers violence, slavery, social status discrimination, and being a single parent. The dark period experienced by the protagonist makes her feel sad, but i, precisely, makes her much stronger to live. It is reflected here how she negotiates with the colonizers in defending his life, although, it does not stop until the end of the colonial period and she lives as a prostitute until the end of her life.